The effect of post-exercise heat exposure (passive heat acclimation) on endurance exercise performance: A systematic review and meta-analysis - Solomon, T. P. J.; Laye, M. J. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background "Active" heat acclimation (exercise-in-the-heat) can improve exercise performance but the efficacy of "passive" heat acclimation using post-exercise heat exposure is unclear. Therefore, we synthesised a systematic review and meta-analysis to answer whether post-exercise heat exposure improves exercise performance.